Spark Discharge Synthesis and Characterization of Ge/Sn Janus Nanoparticles - Anna A. Lizunova; Vladislav I. Borisov; Dana Malo; Andrey G. Musaev; Ekaterina I. Kameneva; Alexey A. Efimov; Ivan A. Volkov; Arseny I. Buchnev; Ivan A. Shuklov; Victor V. Ivanov (Nanomaterials, 2023)
Germanium–tin nanoparticles are promising materials for near- and mid-infrared photonics thanks to their tunable optical properties and compatibility with silicon technology. This work proposes modifying the spark discharge method to produce Ge/Sn aerosol nanoparticles during the simultaneous erosion of germanium and tin electrodes. Since tin and germanium have a significant difference in the potential for electrical erosion, an electrical circuit damped for one period was developed to ensure the synthesis of Ge/Sn nanoparticles consisting of independent germanium and tin crystals of different sizes, with the ratio of the atomic fraction of tin to germanium varying from 0.08 ± 0.03 to 0.24 ± 0.07. We investigated the elemental and phase composition, size, morphology, and Raman and absorbance spectra of the nanoparticles synthesized under different inter-electrode gap voltages and the presence of additional thermal treatment directly in a gas flow at 750 °C. The research shows that the in-flow thermal treatment of aerosol-agglomerated nanoparticles produced special individual bicrystalline Janus Ge/Sn nanoparticles with an average size of 27 nm and a decreasing absorption function with a changing slope at 700 nm.